THEANALYSISOFSPINALINJURIESOFTHEGONDOLAS FOUR-SPRINGBEAMSAFTER 22 YEARSOFOPERATION - Trotskyi, M. V.; Sheleiko, T. V. (Science and Transport Progress, 2008)
The results of inspection of gondola-car center girders with 22-year term of operation are presented. On the basis of results obtained the diagrams of distribution of malfunctions on the length of the center girder are constructed.